2009
DOI: 10.1590/s1413-86702009000200010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fosfomycin activity in vancomycin-resistant Enterococcus faecalis

Abstract: Enterococci are part of the endogenous flora of human beings, are naturally resistant to several classes of antimicrobials, and are able to acquire resistance with relative ease. Currently the vancomycin-resistant enterococci are spread all over the world and treatment options for infections caused by it are often extremely limited. We assessed 193 vancomycin-resistant Enterococcus faecalis isolates collected from four different hospitals in Porto Alegre for their susceptibility to fosfomycin using the E-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…[3,[6][7][8][9][10][11][12][13][16][17][18]In addition, this is the first study to compare clinical outcomes of fosfomycin in the hospital setting for MDR UTIs and associated antibiotic costs. Neuner et al conducted a retrospective chart review of 41 patients treated with fosfomcycin who had a MDR UTI from 2006 to 2010 but did not compare outcomes to other antibiotics traditionally prescribed for these pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,[6][7][8][9][10][11][12][13][16][17][18]In addition, this is the first study to compare clinical outcomes of fosfomycin in the hospital setting for MDR UTIs and associated antibiotic costs. Neuner et al conducted a retrospective chart review of 41 patients treated with fosfomcycin who had a MDR UTI from 2006 to 2010 but did not compare outcomes to other antibiotics traditionally prescribed for these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4] Thus, there is a need for less expensive and effective alternative antibiotics for the treatment of VRE and ESBL UTIs. [5][6][7][8][9] Fosfomycin tromethamine is a synthetic, broad spectrum, bactericidal antibiotic that works by inhibiting pyruvyl transferase during bacterial cell wall synthesis, and it may also decreases bacterial adherence to epithelial cells in the urinary tract. [10] Fosfomycin is available as an orally administered single-dose 3 gram sachet that is mixed with water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, resistance to these agents was reported. 7,14 In this study, we determined that all VR E. faecium isolates were susceptible to fosfomycin. Allerger et al 15 reported that 96% of VRE were susceptible to fosfomycin according to the disc diffusion method.…”
Section: 13mentioning
confidence: 99%
“…Glycopeptide resistance has become a significant problem in nosocomial infections. 7 S. aureus is an important cause of nosocomial bacteremia. Coagulase-negative staphylococci are one of the most common sources of blood-and catheter-associated infections, particularly in hematology and oncology patients.…”
Section: Introductionmentioning
confidence: 99%